Windy night with wild horses - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series, 2024)
"Jack and Annie are whisked away to Mongolia to meet the near-extinct little horses and their caretakers, but can they help protect the last of the horses from predators?"--